Influence of a program for the development of experiential learning in farmers - Alarcón-Diaz, Henry (2019)
The objective of the present study has been to carry out the andragogic program “Organic Crops” for the development of experiential learning. In this research, a group of 60 farmers from a community located south of Lima (Peru) participated. The method used was mixed and was developed in two moments: The first, with a quantitative approach and a quasi-experimental design, data were collected that were submitted to a pretest and post-test through the SPSS software, and the second, with a qualitative approach. They conducted in-depth interviews whose results were analyzed using the Atlas software. You. The quantitative results obtained showed an influence of the program on the experiential learning of the inhabitants. On the other hand, the qualitative results from the interviews show a recognition, value and contribution ofthe program according to the vision of the interviewees